Inflammatory Response and Lung Function Toward Illness Perception of Poultry Farm Workers - Anita Rahmawati; Wahyu Wibisono (Bandung State Polytechnic (Politeknik Negeri Bandung), 2021)
The poultry farm workers should aware to the risk of respiratory disorders. The illness perception represents belief about health condition of the body. The inhaled organic particles at poultry farm area could trigger chain of immunological reactions that begin from the release of neutrophil and lymphocyte up to fibrogenesis resulted in pulmonary dysfunction. The aim of this study was to identify the association between inflammatory response and lung function with illness perception of poultry farm workers.The study used observasional analytic methods with cross sectional design. One hundred and five poultry farm worker were taken as samples which obtained by purposive sampling methods. Illness Perception Questionnaire-Occupational Respiratory Disorder Risk (IPQ-ORDR) was used to measure the illness perception while the inflammatory response was measured by neutrophil levels. The lung function examination resulted in several lung function parameters (FEV1, FVC and FEV1 to FVC ratio). The results showed that there was no association between the inflammatory response and illness perception (p = 0.228) and the lung function was associated with illness perception (p = 0.001). The illness perception is not always match with the actual respiratory health conditions in poultry farm workers. It is needed to provide more information on the risk of respiratory disorders to the poultry farm workers.